Does participation in a court-based trauma-focused evaluation program influence permanency outcomes for children involved in the child welfare system? - Kathleen A. Kemp; Crosby A. Modrowski; Kaitlin Sheerin; Miyah Grant; Charlene Collibee (Child Protection and Practice)
Background: Children involved in the child welfare system, especially those in out-of-home care, experience high rates of mental health symptoms. Mental health symptoms have been linked to worse permanency outcomes in this population. Objective: The present study aimed to evaluate whether children who received a trauma-focused evaluation, compared to children who received usual care, experienced differential permanency outcomes, as well as other court-related outcomes (e.g., legal system involvement). Participants and setting: One-hundred and twenty-five children (58% female, Mage = 10.61) from a family court in the Northeastern United States participated in a trauma-focused evaluation program. Methods: Data for the current study were collected via a retrospective chart. Participants were recruited at a family court of a Northeastern state. Between-groups differences on court-related outcomes were assessed using logistic regression and Kaplan Meier estimates. Findings: There were no significant differences between children who received the trauma-focused evaluation program versus usual care in the likelihood for guardianship changes, termination of parental rights, new child welfare petitions or new juvenile legal petitions. The groups significantly differed in the likelihood of case closure; children who received the trauma-focused evaluation program were more likely to experience case closure compared to children who received usual care. Additionally, on average, children who received the trauma-focused evaluation program achieved case closure almost 8 months sooner. Conclusions: The findings suggest that initiatives aimed at identifying mental health concerns and linking children placed in out-of-home to relevant mental health services care can have a significant and positive impact on permanency outcomes.